EMPOWERING MICRO, SMALL MEDIUM ENTERPRISE (MSMES) THROUGH E-COMMERCE PLATFORMS IN SUKODONO VILLAGE, TAHUNAN DISTRICT, JEPARA REGENCY, CENTRAL JAVA, INDONESIA - Meiryani, Meiryani; Syamil, Ahmad; Deniswara, Kevin; Kurniawan, Bambang Kartono; Angelus, Micheal (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
This community service activity has the spirit to encourage and increase the competitiveness of small and medium enterprises (MSMEs) in Sukodono Village, Tahunan District, Jepara Regency, Central Java in increasing income and improving the Indonesian economy and has proven to be a safety valve for the national economy in times of crisis. Sukodono Village The village has an area of ​​1.8 Ha and consists of 5 hamlets, namely Karang Anyar, Krajan, Sukodono, Kramat, and Sentono. This village is inhabited by around 6,000 people and 2,007 families. The various problems that exist in MSMEs actually make MSMEs unable to compete, running in place, and even going bankrupt. So that MSMEs can increase income, obtain capital by assisting MSMEs in recording financial administration properly and correctly and utilizing e-commerce platforms to increase income, MSME assistance and training are needed that help MSMEs in the process of recording financial administration and going online properly and correctly. in accordance with applicable standards. The aim of this service is to help with the difficulties faced by MSME entrepreneurs in Sukodono Village, Tahunan District, Jepara Regency, Central Java, such as many sales being carried out conventionally, not yet recording financial reports, unorganized inventory and so on. This service activity is planned to be carried out in a hybrid manner, namely onsite and online. The methods used are mentoring/training/workshops and coaching. It is hoped that the results of this service can be used for MSME activities in increasing MSME income so that it can increase the competitiveness of MSMEs so that the contribution of MSMEs to the economic sector will be wider and greater. The results of this activity are that MSMEs in Sukodono Village, Tahunan District, Jepara Regency, Central Java are able to prepare financial reports in accordance with applicable regulations and are able to use and implement digital technology in selling merchandise and it is hoped that this can develop the MSME business in Sukodono Village, Tahunan District, Jepara Regency, Central Java. It is hoped that MSMEs can increase efficiency in managing their finances and increase sales through e-commerce based marketing.